Spatial and temporal variability of the chemical characteristics of food waste and green waste: influence on their sampling and composting. (8th May 2019) - Cestonaro, Taiana; Barros, Raphael Tobias De Vasconcelos; Matos, Antonio Teixeira De
A novel sampling method for characterisation of food and tree pruning wastes was applied. The goal was to identify spatial variability (inside the lot to be sampled) and temporal variability (between lots over time) of the wastes, since these variabilities may influence the sampling process, preparation of the windrows for composting and compost characteristics. The wastes evaluated were those received at the municipal composting facility of Belo Horizonte - MG (Brazil). Different levels of spatial variability (which causes measurement uncertainty) associated with each characteristic of the wastes should be considered in order to increase sampling representativeness. A larger number of composite samples are need for characterisation of the nutrient contents and organic carbon/nitrogen ratio. Temporal variability in tree prunings influenced the set-up of the windrows for composting and the great heterogeneity in food waste can make it difficult to maintain the uniformity of compost nutrients among the batches produced.